Socioeconomic status is not judged equally: Target race shifts standards in interpersonal judgments of SES. (18th May 2018) - Weeks, Matthew
Abstract: Across three studies, respondents made SES judgments of targets varying in Race (White or Black) and SES (Low or High), including global subjective SES, financial success, and educational attainment. As Whites and Blacks are stereotypically associated with upper and lower SES, respectively, the Shifting Standards Model (SSM) of stereotype judgments predicted the pattern of interpersonal objective and subjective judgments. In Study 1, in a between‐subjects design, respondents rated Black targets significantly higher on subjective measures than White targets, even as the targets were rated as comparable on objective measures. Study 2 replicated these effects with a broader range of stimulus materials. In Study 3, the shifting standards effect was replicated using a within‐subjects design, further supporting the effect. The findings support the application of the SSM to race‐based shifts in interpersonal judgments of SES and are discussed regarding their implications for intergroup relations and workplace evaluations.